The Effect of Weekends and Clock Changes on the Sleep Patterns of Children with Autism: A Study of Historical Records - Tim I Williams (Journal of Sleep And Sleep Disorder Research, 2019)
Background Children with autism spectrum disorders (ASD) often have difficulties settling to sleep and maintaining asleep through the night. Sleep difficulties are linked to challenging behaviour so understanding the causes of these difficulties is vital. Possible explanations are: (1) that irregular innate cycles lead to difficulties maintaining/initiating sleep at the appropriate times; (2) that children with ASD fail to learn from the contingencies that teach neurotypical children to initiate and maintain sleep. If the cycles are innate then small externally imposed changes in routine will not affect the sleep cycle. Methods The sleep records of 46 children with autism and moderate to profound intellectual impairments attending a residential school were examined to identify the effects of spring time change and weekend leave on 1) the times children went to sleep, 2) the length of their sleep and 3) the number of sleep disruptions. Manual staff recordings of the children’s sleep were conducted and data for these variables were analysed using repeated measures analysis of variance. Results A later sleep time was found in children regarding their sleep onset on Sunday after the time change (average onset was 9:57 p.m. ((s.e. = 8.49 minutes) versus 10:17 p.m. (s.e. = 8.19 minutes), with analysis of variance of sleep onset time showing a significant effect (F (3,41) = 5.02, p = 0.005). However, only two out of three comparison groups showed statistically significant effects (March 23rd versus March 30th mean difference = 0.39, p = 0.003; March 30th April 13th mean difference = 0.36, p = 0.03). No statistical difference was found between March 30th versus April 6th or other sleep parameters in any groups (i.e., sleep duration or night time awakenings). Similarly, no change in any sleep parameters (i.e., sleep onset or awakenings) were found when Sundays sleep parameters were compared to Mondays and/or Tuesdays. Conclusions In this small pilot study, small changes of day/night cycles appear to have few effects on the sleep patterns of children with ASD attending a residential school. While no significant sleep pattern change was found in this population due to change of clock times or weekend visits, larger epidemiological studies addressing other unexamined variables to better delineate changes in ASD are needed.
Keywords: autism spectrum disorders